Composite hydrogel materials of biomedical application with fungibactericidal properties - Chopyk, Nataliya; Vashchuk, Kateryna; Melnyk, Sofiia; Skorokhoda, Volodymyr (Видавництво Львівської політехніки, 2017)
The new porous compositions on the basis of hydroxyapatite filled copolymers of methacrylic esters and polyvinylpyrrolidone, which containing silver nanoparticles in the structure, were synthesized. Effect of pores forming agent nature, polyvinylpyrrolidone and hydroxyapatite amount on the composite properties was observed. In the composite structure silver nanoparticles are obtained via silver nitrate reduction by tertiary nitrogen of polyvinylpyrrolidone. The synthesized silver-containing composites possesses bactericidal properties .
Keywords: porous composition; polyvinylpyrrolidone; silver nanoparticles; bactericidal properties; porosity